Pemanfaatan Aplikasi Quizizz Pada Pre-Test Dan Post-Test Dalam Pembelajaran Bahasa Indonesia - Anugrah Dinda Juliawan; Anjelia Ratu Oasis; Nur Syamsiyah (Program Studi Magister Pendidikan Bahasa Indonesia FKIP Universitas Mataram, 2025)
The evaluation process in education plays a central role in measuring student achievement levels and the effectiveness of learning. Technology can be used in education to assist with learning and assessment. The Quizizz application is one of the educational technology innovations that capture students' attention. The Quizizz application can be utilized to measure students' understanding levels. This study aims to evaluate the use of the Quizizz application in Indonesian language learning on procedural text material through pre-tests and post-tests. The type of method used is descriptive quantitative. The subjects in this study are the 7.4 grade students at MTsN 4 Bekasi, totaling 29 individuals. The data in this study consists of questionnaire results from 11 questions that were distributed to the 7.4 grade students at MTsN 4 Bekasi. The research instrument used in this study is a questionnaire. The research results show that the Quizizz application can increase student motivation and is effective for use in learning, especially in pre-tests and post-tests. It can be proven from the results of the questionnaire distributed to 29 students, the majority agreed that the Quizizz application is attention-grabbing, easy to use, motivating, more effective, practical, minimizes cheating, saves time and costs. The only obstacle faced is the unstable network connection. This will cause students to join late and lead to additional problems.